Dosimetric and volumetric changes in the rectum and bladder in patients receiving CBCT‐guided prostate IMRT: analysis based on daily CBCT dose calculation - Pearson, David (J Appl Clin Med Phys, 2016)
Delivered dose can be calculated by transferring the planned treatment beams onto the daily CBCT. Bladder and rectum volumetric doses were calculated and correlated to the daily bladder and rectum fullness. Patients for this study underwent hypofractionated prostate IMRT to 70 Gy in 28 fractions. Daily CBCT was utilized for image guidance. A clinically acceptable plan was created using a CTV‐to‐PTV uniform margin of 5 mm. Image fusion was performed to transfer the bladder and rectum contours onto each CBCT. Contours were then edited to match the anatomy of each CBCT. Using the daily treatment isocenter, the planned beams were transferred onto the CBCT and daily and cumulative DVHs calculated. For the results a total of 168 daily CBCTs were evaluated. The bladder was found to be smaller for 74.7% of the 168 daily CBCTs accessed in this study. This reduction in volume correlated to an increase in the cumulative bladder V70 Gy from 9.47% on the planning CT to 10.99% during treatment. V70Gy for the rectum was 7.27% on the planning CT, when all six patients were averaged, and increased to 11.56% on the average of all daily treatment CBCTs. Increases in volumetric rectum dose correlated with increases in rectal volume. For one patient, the rectum and bladder absolute V70 Gy, averaged over the course of treatment, increased by 295% and 61%, respectively. Larger variations in the daily bladder and rectal volume were observed and these correlated to large deviations from the volumetric dose received by these structures. In summary, bladder and rectum volume changes during treatment have an effect on the cumulative dose received by these organs. It was observed that the volumetric dose received by the bladder decreases as the volume of the bladder increases. The inverse was true for the rectum. PACS number(s): 87.55.dk‐, 87.57.Q‐